̶T̶h̶e̶ ̶p̶r̶o̶b̶l̶e̶m̶ ̶o̶f̶ ̶e̶n̶s̶u̶r̶i̶n̶g̶ ̶a̶n̶d̶ ̶p̶r̶o̶t̶e̶c̶t̶i̶n̶g̶ ̶c̶i̶v̶i̶l̶ ̶a̶n̶d̶ ̶p̶o̶l̶i̶t̶i̶c̶a̶l̶ ̶r̶i̶g̶h̶t̶s̶ ̶i̶n̶ ̶t̶h̶e̶ ̶c̶o̶u̶n̶t̶r̶i̶e̶s̶ ̶o̶f̶ ̶C̶e̶n̶t̶r̶a̶l̶ ̶A̶s̶i̶a̶ (RETRACTION) - Dossanova Ә.К.; Iskakova Ж.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article considers the main issues in the field of protection of civil and political rights in the countries of Central Asia. The study examined the historical development and current state of the problem of ensuring civil and political rights in the Central Asian states. In the course of the study, decisions of the United Nations treaty bodies and scientific literature on the topic of the study were examined. In the course of the study, the national legislation of the countries of Central Asia was examined. The study showed that the following civil and political rights and freedoms are seriously violated in the countries of Central Asia: freedom of speech, freedom of assembly and association, freedom of conscience and religion, the right to a fair trial and the right not to be subjected to torture and other cruel acts and forms of punishment. The study proposed a conclusion to consider amending national legislation and forming new mechanisms to ensure civil and political rights in order to protect and safeguard the right to freedom of expression and not to be subjected to torture or other cruel punishment in the countries of Central Asia.